Pulling G Human Responses to High and Low Gravity - Seedhouse, Erik.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Formula 1 racing drivers, figher pilots, astronauts - G forces are an integral part of their lives - How do racing drivers sustain high G loads and not pass out? - What accelerative forces are unleashed when a fighter pilot ejects from a high-performance jet? - What is it like being launched into space and what are the effects on astronauts living in zero G on board the International Space Station? - How do aircraft simulate zero G? Pulling G gives a unique insight into how G forces affect people working inthe high and low G environments. It examines the risks of high and low acceleration and explains the physiology of surviving in these environments. The history of G-related research is described, together with present-day and future development of methods to cope with the effects of increased and reduced G.
Preface -- Acknowledgments -- About the Author -- List of figures -- List of tables -- List of abbreviations and acronyms -- Chapter 1: Project MX981 -- Chapter 2: To black out or not to black out -- Chapter 3: The wobblies -- Chapter 4: The G machine -- Chapter 5: Formula One -- Chapter 6: Punching out -- Chapter 7: Launch and re-entry -- Chapter 8: Microgravity -- Chapter 9: Artificial gravity -- Index.
Keywords: Physics; Biochemistry; Astronomy; Astronautics; Physics; Biophysics and Biological Physics; Popular Science in Astronomy; Aerospace Technology and Astronautics; Medical Biochemistry